Николай Гоголь - Сергеев Анатолий Анатольевич (Исторический роман, 2005)
Экземпляры: С/а ДБ (20101126) / Инвентарный номер: 96683 / Цена: 140 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 32 / ББК: 84(2Рос=Рус)6